An Annotated Edition of Chaucer Belonging to Stephan Batman. (10th June 2021) - Leahy, Conor
Abstract: This article introduces a copy of The Woorkes of Geffrey Chaucer (1561) formerly belonging to the writer, cleric, limner, and book-collector Stephan Batman ( c . 1542–1584). The volume is currently held at the Guildhall Library (SR 2.3.3), and contains Batman's annotations and manicules throughout the text. It also features a 28-line poem in Batman's hand, a short booklist of medieval chronicles, and five line drawings. The book thus offers a fresh insight into the reading practices of one of the most industrious English antiquaries of the sixteenth century, and sheds new light on Chaucer's sixteenth-century reception.